Implementation of Structuring Human Resource Management System to Improve Soldier Professionalism in Order to Realize Bureaucratic Reform in the Indonesian Navy - Surya Hendra Junianto; Dwi Soediantono; M. Al-Amin (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This paper’s background is the bureaucratic reform program in the Indonesian Navy, where the human resource management system arrangement is a priority. The current condition of the arrangement of the human resource management system in the Indonesian Navy is not optimal, which will be analyzed using applicable regulations, human resource management theory, implementation theory, and professionalism theory. This paper compares the conditions of the arrangement of the human resource management system, which is expected to obtain a solution to the problem of the current condition. By optimizing through the methods of education, socialization,